N-Acetyl-cysteine and Mechanisms Involved in Resolution of Chronic Wound Biofilm - Xin Li; Jane Kim; Jiabin Wu; Alaa’ I Ahamed; Yinsheng Wang; Manuela Martins-Green (Journal of Diabetes Research)
Chronic wounds are a major global health problem with the presence of biofilm significantly contributing to wound chronicity. Current treatments are ineffective in resolving biofilm and simultaneously killing the bacteria; therefore, effective biofilm-resolving drugs are needed. We have previously shown that, together with α-tocopherol, N-acetyl-cysteine (NAC) significantly improves the healing of biofilm-containing chronic wounds, in a diabetic mouse model we developed, by causing disappearance of the bacteria and breakdown of the extracellular polymeric substance (EPS). We hypothesize that NAC creates a microenvironment that affects bacterial survival and EPS integrity. To test this hypothesis, we developed an in vitro biofilm system using microbiome taken directly from diabetic mouse chronic wounds. For these studies, we chose mice in which chronic wound microbiome was rich in Pseudomonas aeruginosa (97%). We show that NAC at concentrations with pH < pKa causes bacterial cell death and breakdown of EPS. When used before biofilm is formed, NAC leads to bacterial cell death whereas treatment after the biofilm is established NAC causes biofilm dismantling accompanied by bacterial cell death. Mechanistically, we show that NAC can penetrate the bacterial membrane, increase oxidative stress, and halt protein synthesis. We also show that low pH is important for the actions of NAC and that bacterial death occurs independently of the presence of biofilm. In addition, we show that both the acetyl and carboxylic groups play key roles in NAC functions. The results presented here provide insight into the mechanisms by which NAC dismantles biofilm and how it could be used to treat chronic wounds after debridement (NAC applied at the start of culture) or without debridement (NAC applied when biofilm is already formed). This approach can be taken to develop biofilm from microbiome taken directly from human chronic wounds to test molecules that could be effective for the treatment of specific biofilm compositions.